Solving enterprise applications performance puzzles : queuing models to the rescue - Grinshpan, L. A. (Leonid Abramovich); Wiley InterScience (Online service) (Hoboken, N.J. : Wiley-IEEE Press, 2012)
"Poorly performing enterprise applications are the weakest links in corporation's management chains causing delays and disruptions of critical business functions. This groundbreaking book frames enterprise application performance engineering not as an art but as applied science built on model-based methodological foundation. The book introduces queuing models of enterprise application that visualize, demystify, explain, and solve system performance issues. Analysis of the models discovers and clarifies not obvious connections and correlations among workloads, hardware architecture, and software parameters"--
"This proposed book is the first on the market that frames enterprise application performance engineering not as an art but as applied science built on model-based methodological foundation. The book introduces queuing models of enterprise application that visualize, demystify, explain, and solve system performance issues. Analysis of the models discovers and clarifies not obvious connections and correlations among workloads, hardware architecture, and software parameters"--
Queuing Networks as Applications Models -- Building and Solving Application Models -- Workload Characterization and Transaction Profiling -- Servers, CPUs, and other Building Blocks of Application Scalability -- Operating System Overhead -- Software Bottlenecks -- Performance and Capacity of Virtual Systems -- Model-Based Application Sizing: Say Good-Bye to Guessing -- Modeling Different Application Configurations.
Includes bibliographical references and index.
Print version record.
Keywords: Queuing theory; COMPUTERS -- Software Development & Engineering -- General; Queuing theory; Electronic books